Gender differences in the relationship between bullying victimization and mobile phone addiction among adolescents: the mediating roles of depression and social anxiety - Yue Li; Erlong Tian; Zainudin Bin Abu Bakar; Zakiah Binti Mohamad Ashari (BMC Psychology)
Abstract Background Mobile phone addiction has become a pervasive behavioral issue among adolescents, closely associated with various psychological stressors. Bullying victimization—defined as repeated exposure to peer aggression—constitutes a significant social stressor linked to emotional maladjustment and behavioral problems. Although previous studies have examined the relationship between bullying victimization and mobile phone addiction, the underlying psychological mechanisms remain unclear. Guided by General Strain Theory and the Interaction of Person–Affect–Cognition–Execution (I-PACE) model, this study aimed to investigate the mediating roles of depression and social anxiety in the longitudinal relationship between bullying victimization and mobile phone addiction among adolescents, with particular attention to gender differences. Methods This study employed a three-wave longitudinal design at six-month intervals among 737 Chinese middle school students (Mage = 13.25, SD = 0.76). Bullying victimization was assessed at Time 1, depression and social anxiety at Time 2, and mobile phone addiction at Time 3. Validated measures included Child Bullying Victimization Questionnaire, Patient Health Questionnaire (PHQ-9), Social Anxiety Scale for Children, and Mobile Phone Addiction Scale. Data were analyzed using SPSS 26.0 and AMOS 24.0. Structural equation modeling (SEM) and bias-corrected bootstrapping were employed to test mediation effects. Multi-group analyses were conducted to examine gender differences in the mediation pathways. Results The findings revealed that bullying victimization significantly predicted increased levels of both depression and social anxiety, both of which subsequently positively predicted mobile phone addiction. Both depression (β = 0.02, 95% CI [0.01, 0.04]) and social anxiety (β = 0.03, 95% CI [0.01, 0.05]) served as significant mediators. Gender-specific analyses revealed that social anxiety significantly mediated the relationship among boys, while depression played a significant mediating role among girls. Conclusions The study suggests that bullying victimization contributes to mobile phone addiction in adolescents through emotional distress, specifically depression and social anxiety, with distinct pathways across genders. Intervention efforts should target emotional regulation skills and consider gender-specific psychological responses to bullying victimization in order to reduce adolescents’ dependence on mobile phones.